Kemampuan Pemahaman Konsep Matematika Siswa Melalui Model Problem Based Learning Berbantuan Alat Peraga - Bien, Yusak Imanuel; Ninef, Barnabas; Gella, Netty J. M (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2023)
Concept understanding is the ability to absorb and understand mathematical ideas. This study aims to determine the ability to understand students' mathematical concepts through problem based learning (PBL) models assisted by teaching aids.  This research is a quantitative study with a quasi-experimental model designed in the form of a non-equivalent control group design.  The population in this study were all eighth grade students of SMP Negeri 1 Atap Penmina involving two research classes, one experimental class and one control class, which were taken using simple random sampling technique.  Data collection techniques and instruments used were tests in the form of description questions consisting of pre-test and post-test questions.  The data analysis technique in this study is a prerequisite test, namely the normality test and homogeneity test, then continued by using the independent t-sample test and gain score.  Based on the results of the analysis, it was concluded that the ability to understand mathematical concepts of students in the class that received PBL model learning assisted by teaching aids was better than students who did not receive PBL model learning with the aid of teaching aids.  The display is in the high category with an average gain score of 0,70 while the gain score data for the ability to understand mathematical concepts of students in the control class is 0,16 which is in the low category.